An agent-based ontology fuzzy logic conceptual model for flood warning prediction - Mohd Aris, Teh Noranis; Hamdan, Hazlina; Che Pa, Noraini; Nazeer, Shahrin Azuan (2015)
In this paper, a flood prediction conceptual model that integrates software agent, ontology and fuzzy logic is proposed. The agent role is to provide information on flood based on river level and rainfall by giving notification to users. The ontology organizes flood knowledge in order to support agent communication. Fuzzy logic will be applied to predict uncertain whether situations.